Chocolate mouth rinse: Effect on plaque accumulation and mutans streptococci counts when used by children - Srikanth R; Shashikiran N; Subba Reddy V (Wolters Kluwer Medknow Publications, 2008)
Background: Glucosyltransferases (GTF) play an important role in the adherence of bacteria to acquired pellicle. Cocoa bean husk extract (CBHE) has been shown to possess anti-glucosyltransferase and antibacterial activity. Aim: This study aimed to evaluate the effect of CBHE on plaque accumulation and mutans streptococcus count when used as a mouth rinse by children. Materials and Methods: Scaling of the teeth of the selected children was done and the children were instructed to refrain from their routine oral hygiene practices till the morning of the fourth day; they were instead given a placebo mouth rinse for use during this period. On the fourth day, saliva was collected from each subject for microbiological analysis and plaque was disclosed and scored using the modified Quigley and Hein plaque index; later, the teeth were cleaned. After 1 week, scaling of the subjects was done and they were given CBHE mouth rinse to rinse their mouth, following the above protocol. The data was statistically analyzed using Wilcoxon′s signed rank test. Results: There was a 20.9% decrease in mutans streptococci counts and a 49.6% decrease in plaque scores in the CBHE group as compared to the placebo group, which was highly significant (P value < 0.001). Conclusion: CBHE is highly effective in reducing mutans streptococci counts and plaque deposition when used as a mouth rinse by children.